2019
DOI: 10.1002/cssc.201902445
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Network of C@MoS2 Nanocapsule‐Decorated Cotton Linters Interconnected by Bacterial Cellulose for Lithium‐ and Sodium‐Ion Batteries

Abstract: To protect the structure of MoS2 from collapse, a strong skeleton is expected to help maintain the integrity. In this study, cotton linters burdened with hollow C@MoS2 nanocapsules are added into nutrient medium for the growth of a bacterial cellulose membrane. Benefitting from good conductivity and structural integrity, the resultant fibrous membrane anode gives reversible capacities of 559 and 155 mAh g−1 for Li‐ion batteries and Na‐ion batteries after 100 cycles, respectively. The structural transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In the figure, R s is the ohmic contact resistance of the electrolyte, R ct is to the charge transfer resistance, and R f appears after the first cycle to represent the SEI resistance. 50,51 The fitting results are listed in Table S2. It is apparent that the ZnSe@CoSe 2 /NC composite has the smallest impedance value, indicating that the electrode has good electrical conductivity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the figure, R s is the ohmic contact resistance of the electrolyte, R ct is to the charge transfer resistance, and R f appears after the first cycle to represent the SEI resistance. 50,51 The fitting results are listed in Table S2. It is apparent that the ZnSe@CoSe 2 /NC composite has the smallest impedance value, indicating that the electrode has good electrical conductivity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Figure g, the EIS curves can be divided into two parts, which are composed of a semicircle of a medium–high-frequency region and a straight line of a low-frequency region, and the curve can be fitted by a corresponding equivalent circuit (Figure S4g). In the figure, R s is the ohmic contact resistance of the electrolyte, R ct is to the charge transfer resistance, and R f appears after the first cycle to represent the SEI resistance. , The fitting results are listed in Table S2. It is apparent that the ZnSe@CoSe 2 /NC composite has the smallest impedance value, indicating that the electrode has good electrical conductivity .…”
Section: Resultsmentioning
confidence: 99%
“…The Fe 3 O 4 -BC-CNF electrodes exhibited high flexibility while concomitantly improving the electrochemical performance of the bare BC-CNFs and Fe 3 O 4 NPs (Figure 19d). Zhou et al [312] reported a biological strategy that significantly improved the integrity of the film by introducing cotton linters during the growth of BC (Figure 19e). When compared with BC/glucose (BG)-C@MoS 2 nanofibers without substrate protection and support, the BG-C@MoS 2 composites had an intact fibrous structure that sustained large volume expansion and shrinkage (Figure 19f).…”
Section: Nanocellulose-derived Carbon Materialsmentioning
confidence: 99%
“…e) Fabrication process of BG-C@MoS 2 electrodes and f) the corresponding cross-sectional SEM images. Reproduced with permission [312]. Copyright 2019, Wiley-VCH.…”
mentioning
confidence: 99%
“…Efforts have been directed toward the use of much smaller constituents such as nanobers (NFs) and nanocrystals for cutting-edge applications because of their remarkable properties including high specic surface area, low density, excellent mechanical properties, thermal stability, low cost, biocompatibility, and biodegradability. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Cellulose nanobers (CNFs) are long exible nano-bers with widths of 5-50 nm and lengths in the micron-tosubmicron scale (50-3000 nm). 18 Selective oxidation of the hydroxyl groups to carboxylate groups on the surface of each crystalline cellulose bril, mediated by 2,2,6,6tetramethylpiperidine-1-oxyl (TEMPO) and subsequent mechanical treatment allows the formation of CNFs with increased capacity to immobilize catalytic metal species.…”
Section: Introductionmentioning
confidence: 99%